2021
DOI: 10.1155/2021/9985814
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Mortality Risk among Patients with Gastroenteropancreatic Neuroendocrine Neoplasms: A Registry‐Based Analysis

Abstract: Background. This research is aimed to explore mortality patterns and quantitatively assess the risks of cardiovascular mortality (CVM) in patients with primary gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs). Methods. We extracted data from the Surveillance, Epidemiology, and End Results (SEER) database for patients diagnosed with GEP-NENs between 2000 and 2015. The standardized mortality ratio (SMR) and the absolute excess risk were obtained based on the reference of the general US population. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Furthermore, multivariate competing risk analysis suggested that patients diagnosed at an older age were predisposed to die due to CVD (HR: 54.817, 95% CI: 27.075-110.985). Interestingly, the SMR of CVM was the highest when patients aged 18-49 (SMR, 15.91, 95% CI: 9.19-27.53), similar to the results reported by Sun et al [ 14 ]. We hypothesized that older patients were likely to suffer from worse overall health, decreased immunity, and increased comorbidities such as infection [ 28 ], so they might not have a sufficient life expectancy to develop and die of CVD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, multivariate competing risk analysis suggested that patients diagnosed at an older age were predisposed to die due to CVD (HR: 54.817, 95% CI: 27.075-110.985). Interestingly, the SMR of CVM was the highest when patients aged 18-49 (SMR, 15.91, 95% CI: 9.19-27.53), similar to the results reported by Sun et al [ 14 ]. We hypothesized that older patients were likely to suffer from worse overall health, decreased immunity, and increased comorbidities such as infection [ 28 ], so they might not have a sufficient life expectancy to develop and die of CVD.…”
Section: Discussionsupporting
confidence: 89%
“…Oh et al reported a 20-fold increase in cardiovascular mortality (CVM) in cancer patients from 2000 to 2016 in Korea [ 13 ]. The risk of CVM in gastroenteropancreatic neuroendocrine neoplasm patients was 1.2 times higher than that in the general US population [ 14 ]. Felix et al demonstrated that the risk of CVM in endometrial cancer patients was 8.8-fold higher compared to women in the general population [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…CVM was the primary endpoint of interest, defined by the following six CVDs in the SEER database: (1) diseases of the heart, (2) hypertension without heart disease, (3) cerebrovascular diseases, (4) atherosclerosis, (5) aortic aneurysm and dissection, (6) other diseases of the arteries, arterioles, and capillaries [ 10 , 11 ], while competing events were deaths from BC, other cancers, and other non-cancer diseases.…”
Section: Methodsmentioning
confidence: 99%
“…To clearly describe the mortality of cardiovascular disease, the Fine-Gray sub-distribution hazard model was used in our current study over the follow-up months (up to 227 months), in which the crude cumulative incidence function (CIF) was applied to represent the probability of developing primary and competing events, and the univariate or the multivariable competing risk survival analyses were applied to select independent predictors of cardiovascular disease among patients with pancreatic cancer 15 . In our study, cardiovascular disease was illustrated as death due to the primary event of interest, and the remaining causes of death, such as pancreatic cancer, other cancer, and other non-cancer causes, were illustrated as death due to competing events.…”
Section: Competing Risk Modelmentioning
confidence: 99%